EVALUATION OF SOME BROAD SPECTRUM ANTIPARASITIC DRUGS AGAINST NATURAL STRONGYIE INFECTIONS IN HORSES - K. Saeed; Z. Qadir; S. A. Khan K. Ashraf; S. Nazir (Journal of Animal and Plant Sciences, 2008)
Three anthelmintics Oxfendazole (Oxafex, Glaxo Wellcomc), Ivermectin (Ivomec, MSD) and Albendazole (Farbenda, Farvet) were evaluated against natural strongyle infections in horses. Forty horses naturally infected with strongyle infections were randomly divided into four equal groups A, B, C and D. Horses from group A, B, C were dosed with Oxafex, Ivomec and Farbenda according to manufacture's recommendation. Group D served as an un-medicated positive control. Faecal samples were collected on day zero (day of drug administration), day 14th (post medication) and day 28 (post medication). Egg counts per gram of faeces were determined by Modified McMaster technique. The efficacy of three drugs was evaluated by comparing percent reduction in faecal egg counts on day 14th and day 281h from day zero. The medicated groups were compared with each other and also with the control group. The efficacy of Oxafex, Ivomec and Farbenda was 94.7, 98 and 81% respectively on day l4-post medication. Their efficacy on day 28th post medication was 100%, 96% and 86%, respectively.
Keywords: Horses; srongylosis; round worms; chemotherapy